In Vivo and in Vitro Antiviral Effects of Berberine on Influenza Virus - 吴莹 李季倩 金叶智 吴珺 王谦 郝鈺 (Chinese journal of integrative medicine, 2011)
Objective：To explore the potential effects of berberine on influenza virus infection both in vitro and in vivo.Methods：In vitro anti-influenza virus assays were performed by cytopathogenic effect and neuraminidase assays in Madin Darby canine kidney cells.In vivo anti-influenza virus assays were performed on the viral pneumonia model of mice.The numbers of mice that died within day 2 to day 14 postinfection were recorded to calculate the mortality.On days 2,4,and 6,the viral titers in the lungs were determined by hemagglutination assay;hematoxylin/eosin staining was used to assess the pathogenic changes of lung tissues; the concentrations of tumor necrosis factor-alpha（TNF-α） and monocyte specific chemoattractant molecule （MCP-1） were measured by radio immunoassay or enzyme-linked immunosorbent assay;the concentrations of nitric oxide（NO） and inducible nitric oxide synthetase（iNOS） were detected by colorimetric method;reverse transcription polymerase chain reaction was used to detect the mRNA level of TNF-αand MCP-1.Results： Berberine showed inhibitory effects on cytopathogenic effects and neuraminidase activity of virus,with the therapeutic index 9.69.In vivo,berberine decreased mice mortality from 90%to 55%,reduced virus titers in the lungs on day 2 postinfection（P0.05）.The lung histology scores were 1.50±0.67,4.50±1.00,and 5.50±1.00 in the berberine group on days 2,4,and 6,respectively,which were significantly reduced compared to 2.17±0.22,6.83±0.44,and 8.50±0.33 in the infected group（P0.05）.The productions of NO and iNOS were repressed by berberine compared with those in the infected group（P0.01）.The transcription and expression of TNF-αwere inhibited by berberine on day 4（P0.01） and day 6（P0.05）,and those of MCP-1 were inhibited on day 6（P0.01） compared with the infected group.Conclusions：Berberine exhibited antiviral effects on the influenza virus both in vitro and in vivo.The possible therapeutic mechanism of berberine on influenza-induced viral pneumonia might be inhibiting the virus infection,as well as improving the pathogenic changes by repressing inflammatory substances release